Tinjauan Yuridis Keberadaan Mobil Plat Hitam di PT. Gading Perkasa Mandiri Pekanbaru Menurut Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - ', Jeprialis; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Since 2007, indonesia becoming one thing only country requiring implementation of csr, with its approved law no. 40 year 2007 on limited liability company and is added to the law no. 25 year 2007 on investment. But since then was, obligations with sanctions, only limited word not much implies. Confusion legislators in formulating sanctions provisions, being great opportunities for the company to not carry out corporate social responsibility. Normatively, there is no rule of law that governs about csr implementation mechanism in one rule of law. Interest thesis writer namely; first, to determine the setting of sanctions to companies that do not run the social responsibility of companies in indonesia; second, to determine the mechanism of sanctions to the company that are not running a corporate social responsibility (corporate social responsibility). What kind of legal research used writer is a kind of normative legal research or legal research literature.from the findings of researchers, there are two main thing that can be inferred. First, there is a lot of laws and regulations governing corporate social responsibility, namely the law of state owned enterprises (soes), law investment law corporate law, law of mineral and coal, and many others, however of the many rule of law which set of corporate social responsibility (csr) there is inconsistency makers act are the terms of use csr that would potentially lead to multiple interpretations in practice, then not all the laws that set about csr also includes rules sanctioned therein, and those laws yang the rules include sanctions, also does not explain how the mechanism of sanctions to be implemented. Second, the mechanism of sanctions can only seen in regulation (regulation csr), the automatic mechanism of sanctions is not set in size and only limited to local areas that govern only. Bylaw csr even this will not be able to walk without a forum its function as containers container aspirations, composer planning, also serves to conduct monitoring and evaluation of the implementing csr, as well as provide recommendation results evaluation report addressed to the head of the region is to review furthermore, the regional administrations can be present the or precisely memberian sanctions